Co-occurrence of a Mullerian anomaly and Kallmann syndrome: A case report - Lea C. George; Rebecca Gendelman; Anat Chemerinski; Pierre Lespinasse; Inessa A. Goldman; Sara Morelli (Case Reports in Women's Health)
The evaluation of primary amenorrhea requires a thoughtful assessment for hormonal, structural and/or genetic causes. Although most cases of primary amenorrhea are caused by a single pathology, rarely multiple pathologies may be uncovered. We present the case of a 33-year-old woman with a history of pubertal failure and primary amenorrhea due to Kallmann syndrome. She reported previous short-term use of hormone replacement therapy, with onset of severe pelvic pain and vaginal bleeding following its discontinuation. Her workup revealed concern for uterine didelphys with OHVIRA syndrome on MRI. Surgical exploration revealed a normal-appearing vagina and cervix communicating with the left uterine horn and fallopian tube, a separate, contralateral, obstructed, and engorged right uterine horn with cervix and obstructed vagina, and normal ovaries bilaterally. She underwent laparoscopic resection of the obstructed right hemiuterus with right salpingectomy. Estrogen replacement therapy was initiated postoperatively with cyclic progestins, and she experienced complete resolution of her pain. In the workup of primary amenorrhea, it is important to consider that more than one pathology may be present. A thorough endocrine, genetic, and anatomic evaluation is imperative prior to confirming the diagnosis and initiating treatment. Kallmann syndrome has rarely been reported with Mullerian anomalies; in this case it represents a scenario in which the induction of puberty and menses brought an obstructive anomaly to light. The possibility of co-occurring pathologies should always be considered to provide optimal care to the patient.